2021
DOI: 10.3390/healthcare9050550
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Generation in Chronic Liver Diseases—A Pilot Study

Abstract: The knowledge about coagulation disorders in patients with chronic liver disease changed in the last decade. The aim of this study was to analyze the parameters of thrombin generation in patients with chronic liver disease, as they are the most appropriate biomarkers to explore coagulation. (1) Background: The knowledge about coagulation disorders in patients with chronic liver disease changed in the last decade. The study of thrombin generation in patients with chronic liver disease provides a much more accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Notably, F2 emerged as a significant predictor (P < 0.0001) of mortality in these patients. This is consistent with prior research indicating reduced thrombin production in chronic liver disease, worsening with disease progression (53). Moreover, studies have associated coagulation abnormalities with increased morbidity and mortality in chronic liver disease (54).…”
Section: Discussionsupporting
confidence: 91%
“…Notably, F2 emerged as a significant predictor (P < 0.0001) of mortality in these patients. This is consistent with prior research indicating reduced thrombin production in chronic liver disease, worsening with disease progression (53). Moreover, studies have associated coagulation abnormalities with increased morbidity and mortality in chronic liver disease (54).…”
Section: Discussionsupporting
confidence: 91%
“…Subsequently, the potential for thrombin generation is normal or increased in patients with liver cirrhosis. Antithrombin III (AT‐III) deficiency also indirectly leads to increased thrombin 38 ; however, a decrease in thrombin generation followed by liver disease progression can also occur 39 . For fibrinolysis markers, it suggested that D‐dimer may be a predictive indicator for PVT development in cirrhotic patients; however, it lacks the capability of distinguishing between PVT and liver dysfunction 40 …”
Section: Risk Factors and Pathogenesismentioning
confidence: 99%